Impact of polymorphic variants on the molecular pharmacology of the two-agonist conformations of the human β1-adrenoceptor - Baker, Jillian G.; Hill, Stephen J.; Proudman, Richard G.W. (Public Library of Science, 2013)
β-blockers are widely used to improve symptoms and prolong life in heart disease primarily by inhibiting the actions of endogenous catecholamines at the β1-adrenoceptor. There are two common naturally occurring polymorphisms within the human β1-adrenoceptor sequence: Ser or Gly at position 49 in the N-terminus and Gly or Arg at position 389 in the C-terminus and some clinical studies have suggested that expression of certain variants may be associated with disease and affect response to treatment with β-blockers. The β1-adrenoceptor also exists in two agonist conformations - a high affinity catecholamine conformation and a low affinity secondary agonist conformation. Receptor-effector coupling and intracellular signalling from the different conformations may be affected by the polymorphic variants.